The Difference in Total Cholesterol Levels Between Male Smokers and Non-Smokers Aged 20-50 Years - Humam, Anang Muh. Naufal; Bahraen, Raehanul; Suryani, Dini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Indonesia is ranked third in the world after India and China with the largest number of smokers. LDL, triglyceride, total cholesterol, and HDL levels can all rise and fall due to smoking. While HDL serves to prevent the formation of atherosclerosis, high LDL levels can increase the risk of atherosclerosis. POCT (Point of Care Testing) is one procedure to check total cholesterol levels. The purpose of this study was to determine the difference in total cholesterol levels of male smokers and non-smokers aged 20-50 years in the Kopang Health Center work area in 2023. This study used a cross-sectional approach. The sampling technique in this study was purposive sampling. The results of this study showed that 63.3% were light smokers, 36.7% were moderate smokers and no heavy smokers. A total of 66.7% of smokers had normal total cholesterol levels while 33.3% experienced increased levels. Non-smokers as many as 96.7% had normal total cholesterol levels and 3.3% experienced increased levels. The results of the Chi-square test showed a P value of 0.010, which means P <0.05, so there is a significant difference between the cholesterol levels of smokers and non-smokers. The conclusion is that total cholesterol levels are normal in smoker respondents and total cholesterol levels are high in non-smoker respondents. The recommendation from this study is the importance of reducing cigarette consumption, controlling cholesterol levels regularly, and maintaining a healthy lifestyle to prevent a significant decrease in HDL levels.